THE PRINCIPLE OF HARMONIZATION IN SPATIAL PLANNING OF RURAL AREAS OF THE KYIV SUBURBAN ZONE - Mykhidenko, M. O. (Municipal economy of cities. Series: «Economy science», 2025)
The article explores the principle of harmonization in the spatial planning of rural areas, with a specific focus on the suburban zone of Kyiv. The significance of rural territories in the context of modern global transformations, including economic, social, and environmental dimensions, is emphasized. The research highlights the need for a balanced development approach, as rural areas today serve not only agricultural functions but also play essential roles in preserving biodiversity, ensuring ecological balance, fostering alternative economic activities, and supporting cultural heritage and social stability. The article identifies the key challenges faced by rural areas in the suburban zone of the city of Kyiv, such as depopulation, aging populations, infrastructure degradation, and limited access to innovation, which are exacerbated by urbanization and globalization processes. The decentralization reform in Ukraine has further intensified the demand for effective spatial planning strategies. Special attention is paid to the role of spatial planning in harmonizing functional zones in rural areas, ensuring a sustainable balance between economic development, environmental protection, and the needs of local communities. The core of the article lies in the analysis of the principle of harmonization in the functional and planning organization of rural areas. The paper defines harmonization as the creation of balanced conditions for various land uses: residential, agricultural, industrial, recreational, and nature protection zones. It underscores the importance of ecologically balanced land use, comprehensive planning, flexibility in spatial decisions, active community participation, and economic efficiency as the foundation of sustainable rural development. The article also discusses the specific application of these principles in the suburban zone of Kyiv, identifying how ecological factors, functional zoning, and rational land use can prevent chaotic urban sprawl, preserve natural landscapes, and improve the quality of life in rural areas. The findings contribute to the advancement of spatial planning theory and practice for rural territories in Ukraine.